Options for Increasing the Safety and Improvement of the Protection of Military Mobile Technology - Peter DROPPA; Peter HALGAŠ (Problemy Mechatroniki)
Military vehicles and equipment should be designed with regard to ergonomics, which is important for the protection of the crew. Reliable protection can be achieved by constant technological progress and the improvement of materials, enabling resistance of an attack by mines and improvised explosive devices (IED) placed under the vehicle. The explosion of a device under a vehicle represents a great risk for its crew. This paper is about the protection systems that are using in the World and provide a comprehensive and effective protection of the vehicles. The mainly task of these systems is to safe the crew. The paper divides the protective anti-mine system into the external protection system and internal protection system. Each of these two basic groups is nearly specify in the text and there are also application examples for military mobile technology. In the end to sum the paper up there are some approaches to improvement of safety and protection of the vehicles.